Factors influencing the pursuit of a Master's degree in library and information science - Sagun, Karryl Kim A. (2007)
There are very few literature on the pursuit of a master's degree in library and information science, and much lesser are those in the Philippine setting. In this regard, this study was made to focus on the factors influencing the pursuit of the said degree, according to the responses of MLIS students of the UP ILIS.